Do People Live at Sea Level and the Dead Sea Level Have Different Patterns of Anti-Hypertensive Drugs - Alhroot, Arwa Ali; Alfanek, Alen Fareed; Alkhushman, Muna; Aljariri, Amal Saad Eldeen; Ibrahim, Diana A.; Abeeleh, Farah Mahmoud Abu; Abeeleh, Jaafar Abu; Alkhatib, Ahed J.; Abeeleh, Mahmoud Abu (European Scientific Journal, ESJ, 2017)
Background: people live at various areas of sea level may have different patterns of anti-hypertensive drugs. Such a relation has never been reported in Jordan. Study objectives: the current study investigated how the sea level will impact the prevalence of hypertension in these areas, and how will affect the pharmacological properties of such a population. Methodology: a cross-sectional study design was involved to collect data from study participants. A total of 1000 participants were randomly selected from the two study areas. 500 participants from each. Participants were matched for age and gender. Blood pressure were measured for all participants. Blood samples were withdrawn to investigate the level of angiotensin II. Data was collected through organizing a working excel sheet and was further analyzed through using SPSS version 20. Data was presented as means, standard deviations, frequencies and percentages. The relationships between variables were examined using independent T-test. Significance was measured at an alpha < 0.05. Study findings: the main findings of the present study were that the mean of SBP is significantly higher in the Dead Sea (122.42±10.53 mmHg) than the Sea level area (118.07±11.64 mmHg), (p=0.001). Another significant variable was MBP which its mean was 91.64 ± 8.90 mmHg in the Dead Sea and 89.84 ± 8.72 mm Hg. The difference in the mean was statistically significant (p=0.001). The level of angiotensin II was 8.84 ± 4.65pg/ml in the Dead Sea area and 11.21± 6.05pg/ml in the area of the Sea level. The difference in the mean of the two study areas was not statistically significant (p>0.05). Conclusions: although the level of angiotensin II was not significantly varied between the study areas, but its trend was to be higher in the Sea level area. It was surprised to have higher levels of SBP and MBP in the Dead Sea rather than the Seal level area. It can be implied that the therapeutic options of hypertensive drugs follow different patterns independent of angiotensin II pathways.